Participation in Culminating Tasks of Students in an English Course - Vibar, Regida (JPAIR Institutional Research, 2020)
This research identifies the culminating tasks participated in by the junior and senior college students in an English course for AY 2018-2019 for the students to articulate their thoughts and feelings effectively using the verbal and non-verbal communication skills in a variety of forms and contexts, use of communication for a range of purposes, e.g., to inform, instruct, motivate, and persuade, use multimedia technologies, and assess the global trend using a self-made rubric and communicate deliberately in diverse environments, including multilingual and contextualization to develop critical thinking skills and engage in collaboration and creative manifestations. It used the descriptive survey method to address the objectives that learning is better gained through participation in culminating tasks that have become a major global trend and an educational transformation that makes the classroom productive, creative, and an avenue to develop critical thinking skills. Based on the global educational principle that “no one must be left behind.” This innovation is recommended to be sustained. The culminating tasks in and out of the classrooms can be sustained for better preparedness for the present global society in learning life and career skills in a diversified way of a modern environment. These global trends and ideas are used to combat mediocrity and precautions to sluggishness in keeping abreast of 21st-century skills.